AN EXPLORATORY STUDY OF BARRIERS IN CAREER ADVANCEMENT OF WOMEN AS LEADERS IN HIGHER EDUCATIONAL INSTITUTIONS. - Rakhi Arora, Anuradha Tiwary, (European Economic Letters (EEL), 2024)
Women predominate the teaching profession both in India and abroad because it has always been viewed as a "suitable" profession for them. Despite the high proportion of women in the sector, they are significantly underrepresented in managerial roles, according to statistics. Therefore, it is still a cause for concern that women are underrepresented in senior managerial roles within educational institutions. A review of studies on gender and leadership reveal that women encounter a number of obstacles when applying for leadership and management roles in the educational sector. The purpose of this study was to explore the glass ceiling barriers faced by women in higher educational institutions. A study of 98 faculty members working in higher education sector in NCR region revealed that gender and psychological constraints were the strongest glass ceiling barriers. The lack of experience in administration and family problems cause them to switch their priorities from career to family and fall behind. Women will hold far more senior positions in organisations if they cultivate a mindset that is more focused on their careers.